,Mein Glaubensbekenntnis‘. Leonard Nelsons Brief an David Hilbert - Peckhaus, Volker (Mathematik im Wandel. Anregungen zu einem fächerübergreifenden Mathematikunterricht, Bd. 2)

Die regressive Methode - Peckhaus, Volker (Zwischen traditioneller und moderner Logik. Nichtklassische Ansätze)

Dialog mit Hindernissen: Philosophie und Mathematik - Peckhaus, Volker (Von der Antike bis zur Gegenwart. Erlanger Streifzüge durch die Geschichte der Philosophie)

Active Common-Mode Voltage Cancellation for Three-Phase PWM Rectifier/Inverter Systems based on a New Topology - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert (Proc. 16th IEEE Applied Power Electronics Conf. (APEC))

High Dynamic Control of a Three-Level Voltage Source Converter Drive with Synchronous Motor and Active Front End - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (EPE’01, Graz)

Generalization of orthogonality principle to model solenoidal wound multiwinding transformers - Wallmeier, P. (Conference Record of the 2001 IEEE Industry Applications Conference. 36th IAS Annual Meeting (Cat. No.01CH37248))

Linear Drive System for the NBP Railway Carriage - Henke, M,; Yang, B.; Grotstollen, H.

CAE-tool for optimizing development of switched mode power supplies - Fröhleke, N.; Hahm, D.; Mundinger, H.; Njiende, H.; Wallmeier, P.; Puder, H. (APEC 2001. Sixteenth Annual IEEE Applied Power Electronics Conference and Exposition (Cat. No.01CH37181))

Improved setpoint adjustment for ultrasonic motors - Schulte, T.; Fröhleke, N. (2001 IEEE/ASME International Conference on Advanced Intelligent Mechatronics. Proceedings (Cat. No.01TH8556))

Pitch analysis and control design for the linear motor of a railway carriage - Yang, Bo; Henke, M.; Grotstollen, H. (IEEE Industrial Application Society International Conference (IAS01), Chicago, Illinois, USA)

Enhanced Analysis and Design Issues of a 3 Level DC/DC Converter with Zero Voltage Zero Current Switching - Fröhleke, N.; Schniedermann, M. (9th European Conference on Power Electronis and Applications (EPE01), Graz, Austria)

Development of Power Converter for High Power Piezoelectric Motors - Schulte, T.; Fröhleke, N. (MAGELEC 2001 2nd symposium on electroactive materials and their applications in electrical engineering,Toulouse, France)

Optimization of Inductors in Power Converters Feeding High Power Piezoelectric Motors - Njiende, H.D; Fröhleke, N. (Australian University Power Engineering Conf. (AUPEC'01), Perth, Australia)

Giuseppe Peano, Geometric Calculus According to the Ausdehnungslehre of H. Grassmann. Translated by Lloyd C. Kannenberg. Boston/Basel/Berlin: Birkhäuser 2000 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Hilbert’s Paradox - Peckhaus, Volker; Kahle, Reinhard (Reports Institut Mittag-Leffler)

Automatisierte Optimierung von induktiven Bauelementen für Stromrichteranwendungen - Wallmeier, Peter

Phraseologische Substitution und ihre Funktionen im Text - Ptashnyk, Stefaniya (Wirkendes Wort. Deutsche Sprache und Literatur in Forschung und Lehre. Heft 3/2001)

Фразеологiчні модифiкацiї: термінологічні проблеми [Phraseologische Modifikationen: Terminologische Probleme – ukr.] - Ptashnyk, Stefaniya (Вісник Львівського університету. Випуск 9: Серія іноземні мови)

„Grammatik in Deutsch-Lehrwerken“. Germanisten - Tagung in Karpacz (5.- 7. Sep-tember 2000) - Ptashnyk, Stefaniya; Fraczek, Agnieszka (Convivium. Germanistisches Jahrbuch Polen 2001)

Diagrammatic self-energy approximations and the total particle number - Schindlmayr, Arno; García-González, Pablo; Godby, Rex William (Physical Review B)
There is increasing interest in many-body perturbation theory as a practical tool for the calculation of ground-state properties. As a consequence, unambiguous sum rules such as the conservation of particle number under the influence of the Coulomb interaction have acquired an importance that did not exist for calculations of excited-state properties. In this paper we obtain a rigorous, simple relation whose fulfilment guarantees particle-number conservation in a given diagrammatic self-energy approximation. Hedin’s G0W0 approximation does not satisfy this relation and hence violates the particle-number sum rule. Very precise calculations for the homogeneous electron gas and a model inhomogeneous electron system allow the extent of the nonconservation to be estimated.